Treatment of disorder effects in X-ray absorption spectra beyond the conventional approach. (October 2020) - Kuzmin, Alexei; Timoshenko, Janis; Kalinko, Aleksandr; Jonane, Inga; Anspoks, Andris
Abstract: The contribution of static and thermal disorder is one of the largest challenges for the accurate determination of the atomic structure from the extended X-ray absorption fine structure (EXAFS). Although there are a number of generally accepted approaches to solve this problem, which are widely used in the EXAFS data analysis, they often provide less accurate results when applied to outer coordination shells around the absorbing atom. In this case, the advanced techniques based on the molecular dynamics and reverse Monte Carlo simulations are known to be more appropriate: their strengths and weaknesses are reviewed here. Abstract : Highlights: The effect of disorder on X-ray absorption spectra is reviewed. The strengths and limitations of the RMC-EXAFS and MD-EXAFS methods are discussed. The possibilities of EXAFS analysis from distant coordination shells are presented.